Prevalence of Cardiovascular Diseases Risk Factors among Border Guard Bangladesh Personnel (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: The prevalence of cardiovascular diseases (CVDs) is rapidly increasing at an alarming rate worldwide and is currently considered as the leading cause of death. List of both modifiable and non-modifiable risk factors for CVDs are long and no particular group of people is immune from it.Objectives: To determine the prevalence of CVDs risk factors among the Border Guard Bangladesh (BGB) personnel.Materials and Methods: This descriptive cross-sectional study was conducted from January to December 2017 among 1225 BGB personnel aged over forty years and working in Chattogram Hill Tracts (CHT) of Bangladesh. Respondents’ socio-demographic characteristics, health history and physical activities were collected in a pre-tested questionnaire. Blood pressure (BP), anthropometric and laboratory parameters were measured and categorized as per the standard procedure.Results: Study subjects’ positive family history of hypertension (HTN), ischemic heart disease, diabetes mellitus and bronchial asthma was 9.6%, 1.8%, 7.9% and 14.2% and positive personal history was 11.5%, 2.5%, 9.7% and 5.6% respectively. A positive history of smoking, using Jorda, Gull and extra salt was 20.4%, 8.9%, 3.5% and 16.3% respectively. Among the respondents by systolic BP; elevated BP, stage1 and stage2 HTN was found 41.5%, 17.6% and 5.7% and by diastolic BP it was 20.9%, 10.3% and 6.8% respectively. Nutritional status by body mass index was; obese 1.2% and overweight 52.5% but by waist-hip ratio only 1.7% was obese. Diabetic and pre-diabetic by ‘Fasting plasma glucose’ was 7.5% and 16% in contrary to ‘Oral glucose tolerance test’ was 8.7% and 17.5% subjects respectively. Very high, high and borderline high total cholesterol was found among 5.5%, 15.1% and 37.8%; triacylglycerol was 2.2%, 32.7% and 29.6% and LDL-cholesterol was 6.5%, 8.5% and 22.7% respondents respectively. HDL-cholesterol was found low in 12.9% study subjects.Conclusion: High prevalence of both modifiable and non-modifiable risk factors of CVDs was found among BGB members. Targeted interventions are needed to reduce modifiable risk factors and prevent CVDs.Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 29-32